Fisher hypothesis: East Asian evidence from panel unit root tests - Tai-Hu Ling; Venus Khim-Sen Liew; Syed Azizi Wafa Syed Khalid Wafa (Munich Personal RePEc Archive (MPRA), 2007)
This study finds evidence supportive of Fisher hypothesis in East Asian economies using panel unit root tests, which allow for cross-country variations in the estimation. Among others, one important implication is that monetary policy will be more effective in influencing long-term interest rates and long-run macroeconomic stability in these East Asian economies under regional collaboration.